PERBEDAAN WAKTU PEMBERIAN PAKAN PADA SAPI JANTAN LOKAL TERHADAP INCOME OVER FEED COST - Suharno H. Syukur; Afandi Afandi (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research was conducted at Dolo District, Donggala Regency from April to June 2007. The aim of the research was to identify the effect of feeding time on income, expenditure and income over feed cost of local cattle. The experimental design used was a Randomized Block Design in which the treatment included were feeding time between 7 am to 5 pm, between 7 am to 9 pm, 7 am to 11 pm, between 7 am to 1 am, and between 7 am to 3 am. The results showed that the effect of feeding time was significant on income of local cattle feed cost, and expenditure, but not significant on income over feed cost of local cattle.